Komunitou vedený místní rozvoj v kontextu sociální politiky - Čepelka, Oldřich (Univerzita Pardubice, 2012)
Community-led local development is a new EU tool to solve local needs and opportunities by force of local action groups. The needful scheme is based on development strategies with funding by various EU cohesion funds. There is a set of social issues that could be supported via CLLD as local actors can recognize and solve local problems better and more effectively than centralized bodies. It is true for promoting social inclusion and combating poverty, for social enterprising, social services, enhancing access to lifelong learning, promoting employment etc.
Community-led local development in the context of social policy
Keywords: community-led local development; local action groups; 2014-20 EU period